Modeling the Incidence of Yellowing Diseases to Whiteflies and Alternative Host - Gusde Ida Bagus Gde Pranatayana; I Putu Sudiarta; Ali Nurmasyah (SEAS (Sustainable Environment Agricultural Science), 2021)
Yellowing diseases is one types of plant diseases which are found in some of the centers of cultivation of yard long bean in Bali. The spread of yellowing diseases caused the presence of vector insects, such as whiteflies and alternative host plants, such as weeds and other crops. This problem is then examined through statistical modeling in order to determine the pattern of the relationship between the incidence of yellowing disease with the populations of whiteflies and the alternative host plants. Collection of data on the yellowing disease incidences, the abundance of whiteflies, and the existence of alternative host plants was done through a direct observation in 100 farmer fields in several centers of cultivation of yard long beans in Bali. Determination of the best mathematical model was performed by linear regression analysis with ordinary least squares method. The results indicated that the best models for the relationship between the incidence of yellowing disease (KPK) with the population of whiteflies (KB) as well as the alternative host plants of yellowing were as follows: KPK = 1,2265 KB0,9872 TIAK1,0936 (R2 = 98,43 %; P-value = 0,000). The incidence of yellowing disease was highly significant positively correlated with the population of whiteflies and yellowing symptomatic alternative host plants. The existence of alternative host plants around the field was very decisive in triggering the emergence of yellow virus disease in the crop.